2021
DOI: 10.1128/aac.02073-20
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations of the Inhibition of Escherichia coli AmpC β-Lactamase by Diazabicyclooctanes

Abstract: β-Lactam antibiotics are presently the most important treatments for infections by pathogenic Escherichia coli, but their use is increasingly compromised by β-lactamases, including the chromosomally encoded class C AmpC serine-β-lactamases (SBL). The diazabicyclooctane (DBO) avibactam is a potent AmpC inhibitor; the clinical success of avibactam combined with ceftazidime has stimulated efforts to optimise the DBO core. We report kinetic and structural studies, including four high resolution crystal structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…However, studies under native-MS conditions imply that formation of this +169-Da species is promoted under high-energy conditions, generated either by collisional activation in the gas phase for MS analysis or by incubation at higher temperature in the aqueous phase, and thus formation of the +169-Da species is likely of limited relevance in physiological conditions. ESI-MS condition influenced fragmentation of the covalent modifications of SBLs by other SBLi has also been reported, e.g., desulfation of avibactam ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 79%
“…However, studies under native-MS conditions imply that formation of this +169-Da species is promoted under high-energy conditions, generated either by collisional activation in the gas phase for MS analysis or by incubation at higher temperature in the aqueous phase, and thus formation of the +169-Da species is likely of limited relevance in physiological conditions. ESI-MS condition influenced fragmentation of the covalent modifications of SBLs by other SBLi has also been reported, e.g., desulfation of avibactam ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 79%
“…The kinetic mechanisms of binding of bicyclic boronates to β-lactamases remain to be established; however, it has been observed that these compounds often display very good activity (IC 50 below the mM range) [74,75]. The results of microbiological assays also support the potential of these compounds as broad spectrum β-lactamase inhibitors [76] (Tables 3-5).…”
Section: Boronic Acid Derivativesmentioning
confidence: 91%
“…The reaction of nacubactam produced open ring products, with the piperidine ring assuming a chair conformation ( Figure 6 ) and the carbamoyl-carbonyl oxygen positioned to engage with the backbone NH of A318. Through polar interactions with N346, T316, and K315, the N-sulfate group is 188 securely fixed in the active site ( Lang et al, 2021 ).…”
Section: Nacubactammentioning
confidence: 99%
“…Active regions of AmpC-nacubactam complex where nacubactam was modeled in a single conformation A in which N sulfate is close to Y150. (Adapted from Lang et al, 2021 ).…”
Section: Nacubactammentioning
confidence: 99%
See 1 more Smart Citation